Conclusion on the peer review of the pesticide risk assessment of the active substance potassium iodide - European Food Safety Authority (EFSA Journal, 2013)
The conclusions of the European Food Safety Authority (EFSA) following the peer review of the initial risk assessments carried out by the competent authority of the rapporteur Member State the Netherlands, for the pesticide active substance potassium iodide are reported. The context of the peer review was that required by Commission Regulation (EU) No 188/2011. The conclusions were reached on the basis of the evaluation of the representative uses of potassium iodide as a fungicide on tomatoes, sweet peppers, cucumber, eggplant, strawberries and ornamental flowers in greenhouse and field applications on strawberries. The reliable endpoints concluded as being appropriate for use in regulatory risk assessment, derived from the available studies and literature in the dossier peer reviewed, are presented. Missing information identified as being required by the regulatory framework is listed. Concerns are identified.